Performance Evaluation of a Heat Recovery System Combined with a Helical-Type Heat Exchanger as a Water Heater - I Putu Aris Eka Saputra; Made Sucipta; Hendra Wijaksana (Natural Sciences Engineering and Technology Journal, 2023)
A heat recovery system is a form of reuse of wasted heat energy as a water heater. The water heater is an effort to utilize heat from the work of the compressor without reducing the function of the air conditioner as a room cooler. This study aimed to evaluate the coefficient of performance between standard air conditioners and modified air conditioners with heat recovery systems using a helical-type heat exchanger with a distance of 0 cm between coils. This was an experimental study on a helical-type heat exchanger. Tests were carried out on standard split air conditioners and modified split air conditioners with heat exchangers. The independent variables in this study are variations of the helical type heat exchanger with a distance of 0 cm between the coil and variations in the air setting at the evaporator output. 16ºC, 20ºC and 24ºC. The dependent variable in this study is the coefficient of performance. The evaporator outlet air temperature setting of 16°C has the greatest heat recovery system value, and this is because the evaporator outlet air temperature setting of 16°C has the largest h2 value compared to other evaporator outlet air temperature settings. The greater the evaporator output air temperature setting, the greater the value of the resulting heat recovery system. In conclusion, the highest coefficient of performance is found at the evaporation exit temperature of 24ºC, and the variation in the distance between the coil is 0 cm. Meanwhile, the hottest water temperature is found in the evaporator air setting of 16ºC with a variation of the distance between the coil of 0 cm.